Rural electricity system reliability: Do outages exacerbate spending on backup fuel in rural Tanzania? - Muhihi, Bikolimana Giliadi; Paschal, Lusambo Leopold (Journal of Energy in Southern Africa, 2022)
Most rural Tanzanians have had no access to electricity. But efforts have been made to remedy this, including an extension of the national grid and the establishment of independent power plants in rural areas. The result is a recordable increase of people with access to electricity; however, the realization of reliable power for both consumers and suppliers has remained a puzzle. This paper out to examine the reliability of rural electricity systems based on consumer measures; to find out determinants for system reliability; and examine how outage incidences exacerbate households’ expenditure on backup fuels. Reliability was assessed through a stepwise approach, where a general system reliability index and trend analysis were used. It was found that system reliability was enhanced because consumers only spent 6–15 days per year without electricity due to outages. These are tolerable outages, given the volatility of the rural system. Further, weather, fire outbreaks in bushes, and lightning, significantly determined system reliability. Nonetheless, despite the reasonable reliability, some outage incidences had dragged consumers into unplanned expenditure on backup fuel. It is recommended that there should be a continuous inspection of the system, and the use of supervisory control and data acquisition device on the distribution line for accurate monitoring is imperative.